Effectiveness of Early Warning Scores for Early Severity Assessment in Outpatient Emergency Care: A Systematic Review - Amaya Burgos-Esteban; Amaya Burgos-Esteban; Vicente Gea-Caballero; Vicente Gea-Caballero; Patricia Marín-Maicas; Azucena Santillán-García; Azucena Santillán-García; María de Valvanera Cordón-Hurtado; Elena Marqués-Sule; Marta Giménez-Luzuriaga; Marta Giménez-Luzuriaga; Raúl Juárez-Vela; et al. (Frontiers Media S.A., 2022)
Background and ObjectivesPatient assessment and possible deterioration prediction are a healthcare priority. Increasing demand for outpatient emergency care services requires the implementation of simple, quick, and effective systems of patient evaluation and stratification. The purpose of this review is to identify the most effective Early Warning Score (EWS) for the early detection of the risk of complications when screening emergency outpatients for a potentially serious condition.Materials and MethodsSystematic review of the bibliography made in 2022. Scientific articles in Spanish and English were collected from the databases and search engines of Pubmed, Cochrane, and Dialnet, which were published between 2017 and 2021 about EWSs and their capacity to predict complications.ResultsFor analysis eleven articles were selected. Eight dealt with the application of different early warning scores in outpatient situations, concluding that all the scoring systems they studied were applicable. Three evaluated the predictive ability of various scoring systems and found no significant differences in their results. The eight articles evaluated the suitability of NEWS/NEWS2 to outpatient conditions and concluded it was the most suitable in pre-hospital emergency settings.ConclusionsThe early warning scores that were studied can be applied at the pre-hospital level, as they can predict patient mortality in the short term (24 or 48 h) and support clinical patient evaluation and medical decision making. Among them, NEWS2 is the most suitable for screening potentially deteriorating medical emergency outpatients.